The Effect of Latitude on Success Rate of Rukyat Hilal at Observatorium Lhoknga Aceh - Machzumy (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2019)
Rukyat hilal of the month of Qamariah, especially the beginning of Ramadan,and Shawwal is a study of falak which often attract attention because of thefrequent differences. This is motivated by the uncertainty of rukyat results dueto the lack of observable rukyat results. This is one of them caused by thelocation of the rukyat which is not safe enough from various naturaldisturbances, such as high rainfall caused of latitude. Lhoknga Observatory islocated at 50 27’ 59, 85” N and 950 14’ 31,87” E, with an altitude of 8 m, and is 15m from the sea. But from 5 years of observation of the new moon, only one timesucceeded in destroying the hilal. The research method uses descriptiveanalytical methods, collecting data by means of documentation and directobservation. The results of this study found that one of the causes of the lowsuccess rate of rukyatul hilal in the observatory was due to its relatively highrainfall which reached an average of 354 mm in years. This rainfall is stronglyinfluenced by the latitude and geographical state of the observatory flanked bythe sea and mountains